The Role Of Workers Organization And Wage Level In Improving Employee Productivity In Electronic Companies In West Java, Indonesia - Sabil (International Publisher (YAPENBI), 2023)
The role of workers' organizations is significant for companies and employees because it impacts wage levels and employee productivity. This study aims to analyze the effect of workers' organizations on wage levels and the effect of workers' organizations and wage levels on work productivity in electronic companies. This research is a type of quantitative research where data is collected by sharing questionnaires with 200 employees who work in the electronics sector in West Java, Indonesia. Data analysis techniques used are descriptive statistics and structural equation modeling (SEM) using PLS.3 software. The results show that Workers' organization directly affects work productivity with significant (0.004 <0.05), Workers' organization directly affects wage level with significance (0.000 <0.05), Wage level directly affects work productivity with insignificant matter (0.986 >0.05), The indirect effect of Workers' organization on Work productivity is through Wage level. P Values are 0.986>0.05, and the impact is not significant.